Kajian Hubungan Antara Iklim Keselamatan Psikososial (Psychosocial Safety Climate) dengan Perundungan di Tempat Kerja (Workplace Bullying) di PT.WID - Wahyuningtias, Ika; Erwandi, Dadan; Nasri, Sjahrul Meizar; Kadir, Abdul (UI Scholars Hub, 2021)
This study aims to determine and examine the relationship and influence of the Psychosocial Safety Climate on the incidence of workplace bullying at PT WID (a power generation company) involving six power plant work areas throughout Indonesia. Method: This was a cross-sectional study involving 100 workers in the power plant industry who were above 17 years of age and with a work experience of at least six months. These workers participated in this study by filling out the Psychosocial Safety Climate (PSC 12) to measure the level of psychosocial safety climate and Negative Acts Questionnaire-Revised (NAQ-R) to determine the incidence of bullying in companies Results: The results of the analysis show that the Psychosocial Safety Climate has a significant effect on the incidence of bullying in the workplace in the company, with a negative relationship direction and moderate strength(p-sig=0,003; r=0,292; ß=-0,257). In addition, the results of multiple linear regressions show that Management Commitment has a significant effect (p-sig = 0.013) on the decrease in bullying levels in the workplace, compared to Management Priority, Organizational Participation, and Organizational Communication. Conclusion: This shows that if there is an increase in one level of Psychosocial Safety Climate, there will be a decrease in bullying actions by 0.257. Where management commitment is the variable that has the most dominant influence on reducing the level of bullying in the workplace.